Transesterification of diethyl oxalate with phenol using MoO3/SiO2 catalyst - Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Applied Catalysis A-General, 2005)
Transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in liquid phase using MoO3/ SiO2 solid acid catalyst with high conversion and 100% selectivity. A series Of MoO3/SiO2 catalysts with different Mo loadings (1-20 wt%) were prepared using sol-gel technique and characterized using X-ray diffraction analysis (XRD), BET specific surface area, temperature-programmed desorption (TPD) of ammonia, and FTIR spectroscopic analysis of adsorbed pyridine. XRD analysis revealed the amorphous nature of the catalyst up to 10 wt% MoO3 loading and the formation of crystalline α-MoO3 phase on amorphous silica support with higher MoO3 loading. BET surface area showed high surface area for catalysts prepared by sol-gel technique with lower MoO3 content; the surface area decreases with increasing MoO3 loading. Ammonia TPD shows much higher acid strength compared to the catalysts prepared by impregnation technique. Among the series of catalysts prepared, MoO3/SiO2 containing 1 wt% MoO3 was found to be the most active catalyst for transesterification reaction, with a maximum DEO conversion of 80.9 and 100% selectivity for DPO. The effects of reaction temperature and catalyst concentration on conversion and product selectivity have been investigated. © 2005 Elsevier B.V. All rights reserved.
Keywords: diethyl oxalate; diphenyl oxalate; MoO3/SiO2; sol-gel technique; transesterification

Regioselective nitration of cumene to 4-nitro cumene using nitric acid over solid acid catalyst - Mathew, Sanyo M.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Catalysis Communications, 2006)
The regioselective nitration of cumene to 4-nitro cumene (4-NC) has been carried out using 70% nitric acid over MoO3/SiO2 solid acid catalyst with high conversion (62%) and selectivity (68%) for 4-NC. A series of MoO3/SiO2 catalysts with different MoO3 loadings (1-20 mol%) were prepared by sol-gel technique and characterized using different characterization techniques. XRD analysis revealed the amorphous nature of the catalyst up to 10-mol% MoO3 loading and formation of alpha-MoO3 crystalline phase on amorphous high surface area mesoporous silica support at higher MoO3 loading. Maximum conversion and selectivity has been obtained with slower addition of nitric acid and simultaneous azeotropic removal of water formed during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cumene; nitration; ring nitration; side chain nitration; solid acid catalyst

Selective cis-dihydroxylation of olefins using recyclable homogeneous molybdenum acetylide catalyst - Biradar, Ankush V.; Sathe, Bhaskar R.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Journal of Molecular Catalysis A-Chemical, 2008)
Selective cis-dihydroxylation of various olefins has been carried out using molybdenum acetylide complex CpMO(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as an efficient and environmentally benign oxidant. In case of cyclohexene, very high conversion (95%) and selectivity (86%) for cis-dihydroxylated product has been achieved using H2O2 as an oxidant and t-butanol as a solvent. cis-Dihydroxylation of other substrates like styrene, a-methyl styrene, limonene and cyclopentene has also been carried out with very high selectivity for diol. The catalyst and intermediate species have been characterized using FT-IR, UV-vis spectral analysis and XPS studies as well as cyclic voltametric studies. These studies suggest that molybdenum oxo-peroxo complex is the catalytically active species. The intermediate blue complex when characterized by ESI MS suggested the formation of dimeric molybdenum complex and XPS and cyclic voltametric studies confirm the presence of mixed valence Mo(V) and Mo(VI) in the reaction intermediate. Based on the characterization results possible mechanism for dihydroxylation is proposed. Interestingly, even though the catalyst is homogeneous; it could be recovered quantitatively by extraction in aqueous phase and recycled five times without any appreciable loss in cyclohexene conversion and selectivity for cis-1,2-cyclohexanediol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: acetylide complex; cis-dihydroxylation; Homogeneous catalysis; Hydrogen peroxide; recyclable

Selective N-oxidation of aromatic amines to nitroso derivatives using a molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Kotbagi, Trupti V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2008)
The molybdenum acetylide oxo-peroxo complex obtained in situ by the treatment of the corresponding molybdenum acetylide carbonyl complex, CpMo(CO)(3)(C CPh); Cp = eta(5-)C(5)H(5) with H(2)O(2), has been used as an efficient catalyst for selective N-oxidation of primary amines to nitroso derivatives. Excellent amine conversion (up to 100%) and very high selectivity for nitroso compounds (99%) have been obtained using 30% hydrogen peroxide as an oxidant. The oxo peroxo, Mo(VI) complex has also been found to be very active for the oxidation of various substituted primary aromatic amines with electron donating as well as electron withdrawing substituents on the aromatic ring. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aromatic amine; Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; nitroso; Oxidation; Oxo-peroxo

Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Selective oxidation of aromatic primary alcohols to aldehydes using molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2009)
Selective oxidation of various aromatic alcohols to aldehydes has been carried out with very high conversion (90%) and selectivity (90%) for aldehydes using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as environmentally benign oxidant, Water-soluble Mo acetylide oxo-peroxo species is formed in situ after reaction of I with aqueous hydrogen peroxide during the Course of reaction as catalytically active species. Interestingly even though the catalyst is homogeneous it Could be recycled very easily by separating the products in organic phase and catalyst in aqueous phase using separating funnel. Even after five recycles no appreciable loss in alcohol conversion and aldehyde selectivity was observed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; Oxidation; Oxo-peroxo; Primary aromatic alcohol

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation

Isolation, characterization, and identification of catalytically active species in the MoO3/SiO2 catalyst during solid acid catalyzed reactions - Kotbagi, Trupti V.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Chemcatchem, 2013)
We report the isolation, characterization, and identification of the catalytically active species formed during various acid-catalyzed reactions if silica-supported MoO3 was used as a catalyst. We have reported previously the synthesis and extensive characterization of the silica-supported MoO3 catalyst prepared by the sol-gel process with ammonium heptamolybdate and ethyl silicate-40 as molybdenum and silica precursors, respectively. The TEM images showed uniformly distributed MoO3 nanoparticles on the high-surface area mesoporous silica support and high acidity (0.9mmolg-1) by using temperature-programmed desorption of ammonia (NH3-TPD) analysis. This catalyst has already shown high activity for various acid-catalyzed reactions. To understand the nature of catalytically active species formed during the reaction, the liquid-phase esterification of acetic acid and ethanol was studied as a probe reaction with very high acid conversion (83%) in 8h. During esterification, the reaction mixture turned blue, which indicated a change in the nature of the catalyst under reaction conditions. These catalytically active species formed in the reaction mixture were isolated and extensively characterized by using FTIR, Raman, powder XRD, BET surface area, NH3-TPD, energy dispersive X-ray, and TEM analysis. The characterization results revealed the insitu formation of silicomolybdic acid on the silica surface in the presence of water, which acts as catalytically active species responsible for the acid-catalyzed reactions.
Keywords: esterification reactions; heterogeneous catalysis; Molybdenum; silicon; sol-gel processes

One-pot synthesis of ultrasmall MoO3 nanoparticles supported on SiO2, TiO2, and ZrO2 nanospheres: an efficient epoxidation catalyst - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Biradar, Ankush V. (Journal of Materials Chemistry A, 2014)
Ultrasmall molybdenum oxide (MoO3) nanoparticles supported on various (SiO2, TiO2 or ZrO2) nanospheres were synthesized in one pot using a reverse micelle method. The prepared catalysts were thoroughly characterized by various physico-chemical methods. TEM images showed uniform dispersion of MoO3 nanoparticles (1.5-4 nm) onto silica (similar to 275 nm). No separate MoO3 particles were identified from TEM for MoO3/TiO2 (similar to 10.5 nm) and MoO3/ZrO2 (similar to 6.5 nm) because AHM reacted with titanium and zirconium hydroxides to form solid solution. Among the prepared catalysts MoO3/SiO2 showed excellent catalytic activity (up to 90% conversion and 100% epoxide selectivity) for olefin epoxidation. The catalyst was successfully recycled up to five cycles without losing much activity and selectivity.

Palladium nanoparticles supported on magnesium hydroxide fluorides: a selective catalyst for olefin hydrogenation - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (ChemCatChem, 2014)
A one-pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol-gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol-gel method led to high surface area (>135 m(2)g(-1)), mesoporous catalysts (pore volume=0.19-0.23 cm(3)g(-1), pore diameter=3-5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47%) was obtained with 1 wt% palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100% conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; magnesium fluorides; Palladium

Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Calcium phosphate nanocapsule crowned multiwalled carbon nanotubes for pH triggered intracellular anticancer drug release - Banerjee, Shashwat S.; Todkar, Kiran J.; Khutale, Ganesh V.; Chate, Govind P.; Biradar, Ankush V.; Gawande, Manoj B.; Zboril, Radek; Khandare, Jayant J. (Journal of Materials Chemistry B, 2015)
We report calcium phosphate (CaP) nanocapsule crowned multi-walled carbon nanotubes (CNT-GSH-G4-CaP) as a novel platform for intracellular delivery of an anticancer drug. As a proof-of-concept, CNT-GSH-G4-CaP demonstrates release of anticancer drug doxorubicin hydrochloride (DOX) within intracellular lysosomes from the interior cavity of CNT upon pH triggered CaP dissolution. Importantly, we found that the CNT with a CaP nanolid can efficiently prevent untimely drug release at physiological pH but promotes DOX release at increased acidic milieu as observed in subcellular compartments such as lysosomes (similar to 5.0). This ``zero premature release'' characteristic is of clinical significance in delivering cytotoxic drugs, by reducing systemic toxicity and thus beneficial for the effective anticancer treatment. We envision that this pH triggered CaP crowned CNT nanosystem would lead to a new generation of self-regulated platforms for intracellular delivery of a variety of anticancer drugs.

Core-shell nanoparticles: synthesis and applications in catalysis and electrocatalysis - Gawande, Manoj B.; Goswami, Anandarup; Asefa, Tewodros; Guo, Huizhang; Biradar, Ankush V.; Peng, Dong-Liang; Zboril, Radek; Varma, Rajender S. (Chemical Society Reviews, 2015)
Core-shell nanoparticles (CSNs) are a class of nanostructured materials that have recently received increased attention owing to their interesting properties and broad range of applications in catalysis, biology, materials chemistry and sensors. By rationally tuning the cores as well as the shells of such materials, a range of core-shell nanoparticles can be produced with tailorable properties that can play important roles in various catalytic processes and offer sustainable solutions to current energy problems. Various synthetic methods for preparing different classes of CSNs, including the Stober method, solvothermal method, one-pot synthetic method involving surfactants, etc., are briefly mentioned here. The roles of various classes of CSNs are exemplified for both catalytic and electrocatalytic applications, including oxidation, reduction, coupling reactions, etc.

Highly loaded well dispersed stable Ni species in NiXMg2AlOY nanocomposites: application to hydrogen production from bioethanol - Fang, Wenhao; Paul, Sebastien; Capron, Mickael; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (Applied Catalysis B-Environmental, 2015)
Inexpensive NiXMg2AlOY nanocomposites with high Ni content (Ni wt% > 40%) are developed as efficient catalysts for the sustainable hydrogen production from a mixture of ethanol and water at low temperature. The NiXMg2AlOY nanocomposites are composed of small and uniform nanoparticles (4-6 nm) of NiO, Ni-Mg-(Al)-O and/or MgO. The strong interactions existing between Ni2+ cations and Mg2+ and/or Al3+ cations either in the Ni-Mg-(Al)-O solid solution and/or at the interface of nanoparticles of NiO and/or Ni-Mg-(Al)-O make the catalyst highly active and stable. The behavior of the solids is analyzed in the presence of low and high concentrations of ethanol while maintaining a H2O/EtOH molar ratio of 3. The NiXMg2AlOY catalysts are shown to be efficient toward H-2 production between 250 and 650 degrees C. In the presence of low concentration of ethanol, on the highly loaded Ni compound (Ni12Mg2AlOY), total conversion of ethanol is obtained at 250 degrees C without formation of CO and carbon, and at 300 degrees C a H-2 yield of 3 mol moletEtOH(-1) is obtained without the formation of CO, exhibiting a remarkable stability with the time on stream even if some carbon is formed. In high concentration of ethanol, total conversion of ethanol is obtained at 450 degrees C on the highly loaded Ni compound (Ni12Mg2AlOY). In such conditions, a stable co-generation of carbon nanofibrous materials which amount increases with Ni content is also obtained. The catalytic stability is related to the type and morphology of the carbon species formed. The correlations among the catalyst properties, the catalytic performances and the characterizations are thoroughly discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrogen; Nanofibrous carbon; nickel oxide; Steam reforming

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids

Trifunctional mesoporous silica-based, highly active catalyst for one-pot, three-step cascade reactions - Biradar, Ankush V.; Patil, Vijayshinha S.; Chandra, Prakash; Doke, Dhananjay S.; Asefa, Tewodros (Chemical Communications, 2015)
We report the synthesis of a trifunctional catalyst containing amine, sulphonic acid and Pd nanoparticle catalytic groups anchored on the pore walls of SBA-15. The catalyst efficiently catalyzes one-pot three-step cascade reactions comprising deacetylation, Henry reaction and hydrogenation, giving up to similar to 100% conversion and 92% selectivity to the final product.

Bicinchoninic acid-based colorimetric chemosensor for detection of low concentrations of cyanide - Biradar, Archana A.; Biradar, Ankush V.; Sun, Tiffany; Chan, Yung; Huang, Xiaoxi; Asefa, Tewodros (Sensors and Actuators B-Chemical, 2016)
Bicinchoninic acid (BCA) is reagent that is widely used to determine the concentration of proteins in solutions through the colored complex it forms with Cu(I) and the proteins. In this report, we present a new use for BCA, where a highly sensitive method for detection of cyanide ions in solutions by using Cu2+-BCA complex as the chemosensing agent is demonstrated. The detection of cyanide ions is achieved by taking advantage of the nucleophilic attack of the Cu2+-BCA complex by cyanide ions. Upon the addition of cyanide ions, the Cu2+-BCA complex undergoes transformations to free BCA via a series of equilibriums and, as a result, forms different Cu(II)-(BCA)(x)(CN)(y) species depending on the concentrations of cyanide ions in the solution. These different Cu(II)-(BCA)(x)(CN)(y) species, in turn, give different metal-to-ligand charge transfer electronic spectra and colors that are easily detectable both with naked eyes and UV-vis spectroscopy. As the cyanide ion concentration increases, the color of the solution containing the complexes changes from green to purple, red, yellow, and finally colorless, giving a corresponding blue shift in the absorption maxima on their UV-vis spectra. Through this process, the complexes enable detection of cyanide ions with a detection level of up to 0.06 ppm in solutions. Thus, this colorimetric technique based on Cu2+-BCA can make low concentrations of cyanide detectable, well before the concentrations possibly reach lethal amounts. Furthermore, the method is shown to give fast detection response with no interference from other anionic and cationic species and has the potential to be adopted for accurate and convenient analysis of cyanide ions in drinking water sources as well as industrial effluents. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BCA; Bicinchoninic acid; Chemosensor; Colorimetric sensor; Copper; Cyanide

Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP